A review of biological effects and treatments of inhaled depleted uranium aerosol. (October 2020) - Ran, Yonghong; Wang, Shuang; Zhao, Yazhen; Li, Juan; Ran, Xinze; Hao, Yuhui
Abstract: Depleted uranium (DU) is primarily used for DU bombs and DU tanks in the military. Aerosol inhalation is considered the primary route of DU exposure. Although laboratory tests have confirmed that inhalation of DU aerosol can cause lung, kidney, and other organ damage, epidemiological studies have found no conclusive evidence that persons in areas with prolonged exposure to DU-containing bombs are affected. After the body inhaled DU aerosols, we first clear the insoluble DU through whole-lung lavage (WLL). Then we eliminate the soluble uranium by the chelating agent. Besides, reducing DU damage to tissues and cells through drugs is also an important treatment method. In future research, emphasis should be placed on the damage mechanism of DU aerosol, the laboratory and clinical research of DU chelating agents, the research on the combination of DU chelating agent and WLL, and the research and development of new drugs to prevent DU damage. Highlights: The formation and characteristics of DU aerosol and its main route into the body. Inhalation of DU aerosols can cause organ damage. No smoking gun that living long-term in DU exposure regions will be affected. The treatment methods were summarized: WLL, chelating agent, drugs protect. Future research focus: damage mechanism, the chelating agent binds to WLL, new drugs.